Haemolymph protein profile of the edible oyster, Crassostrea madrasensis (Preston) exposed to different salinities - George, K C; Ittoop, Gijo; Thomas, P C; Shobhana, K S; Sanila, N K; Paulton, M P; Nisha, P C (Indian Journal of Fisheries, 2011)
The haemolymph total protein concentration and protein profile of C madrasensisexposed to different salinities were studied. The animals were maintained atsalinities 6 ,12,24 and 36 ppt for one month. The serum total protein concentrationshowed significant reduction at 6 and 36 ppt. The haemolymph protein profileobtained by SDS-PAGE also varied with difference in salinities. There werefour bands with molecular weight 86,74,31 and 26 kDa in all the four groups. Theintensity of bands was higher in groups maintained at 12 and 24 ppt compared toother groups. The haemolymph of animals maintained at 6 ppt also showed threeadditional bands of 60, 52 and 13 kDa that were feebly expressed